Dynamic simulation and vibration test of tooth breakage fault for metro gearbox - WANG Zhengbing; YANG Ya; LIN Jinghui; YUE Zihao (Jixie qiangdu)
Metro gearbox is a key component for torque transmission in vehicles, and its failure will directly affect the safety of train operation. The vibration characteristics of tooth breakage faults in metro gearbox were studied by combining dynamic simulation and vibration test. Firstly, based on the dynamic relationships and constraint characteristics between various components of metro gearbox, a rigid-flexible coupling dynamic model of metro gearbox with tooth breakage faults was established through the impact function method, Coulomb friction model, bearing modeling, flexible body of the housing and gear system dynamics theory. The dynamic response of the gearbox under different types of tooth breakage faults was studied, and the influence of operating parameters on the vibration characteristics of tooth breakage was analyzed. Then, through vibration test, the dynamic response of metro gearbox under normal state and broken tooth fault was obtained, verifying the accuracy of the dynamic simulation model. The results indicate that the rigid-flexible coupling dynamic model can effectively calculate the acceleration response of gearbox in different operating states, provide diagnostic basis for the prediction and identification of tooth breakage faults in the gearbox.